Pharmacogenomics and Precision Pharmacotherapy in Heart Failure: A Narrative Review - Andika Yusuf Ramadhan (MEDICINUS, 2026)
Heart failure is a life-threatening condition affecting approximately 1% of the global population, with its prevalence continuing to rise. Genetic factors, including pathogenic variants in sarcomere, cytoskeletal, and ion channel genes, contribute to disease progression, often following Mendelian inheritance patterns. However, most interindividual variability in disease course and therapeutic response arises from polygenic, non Mendelian patterns, particularly single nucleotide polymorphisms (SNPs). SNPs can modestly influence gene expression, protein function, and downstream signaling pathways, thereby affecting the pharmacokinetics and pharmacodynamics of cardiovascular drugs. Variants in genes such as CYP2D6, ACE, AGT, CYP11B2, ADRB1/2, SLC5A2, and UGT2B4 have been associated with differential responses to β-blockers, SGLT2-inhibitors, and ACE inhibitors. The clinical application of genomic approaches remains limited due to small study sizes, interpatient variability, and the lack of standardized biomarkers. Nevertheless, integrating genetic, epigenetic, and phenotypic data offers a promising strategy to guide more effective and individualized heart failure pharmacotherapy.